2007
DOI: 10.1182/blood-2007-04-088088
|View full text |Cite
|
Sign up to set email alerts
|

Anti-BR3 antibodies: a new class of B-cell immunotherapy combining cellular depletion and survival blockade

Abstract: [1][2][3][4] Since approval of a depleting anti-CD20 monoclonal antibody (mAb) (rituximab [Genentech, South San Francisco, CA; Biogen-IDEC, Cambridge, MA; Roche, Basel, Switzerland)] in 1997 for the treatment of non-Hodgkin lymphoma (NHL), almost 1 million patients have been treated with rituximab as a first or second line therapy, either alone or in combination with chemotherapy. In addition, rituximab maintenance therapy significantly prolongs tumor remission and patient survival in patients with indolent B-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 61 publications
4
51
0
1
Order By: Relevance
“…Thus, the differences in secondary lymphoid organ phenotypes between our NIK KO/KO mice and NIK aly/aly mice, as well as the other NIK-deficient mouse strain, may arise from Upon acute deletion of NIK in adult mice using our conditional NIK KO allele, we observed the abrogation of noncanonical NF-kB signaling, as assessed by p52 production, and a resulting reduction in B cell numbers in lymph nodes and spleen. These reductions in B cell populations are similar to what was observed upon blockade of BAFF signaling in adult mice (52) produced in BAFF-deficient and BR3/BAFF-R-deficient mice (61), these effects of NIK deletion likely reflect roles for NIK and the noncanonical NF-kB pathway in non-BAFF-driven biology. Given that CD40L/CD40 signaling is required for germinal center formation and the production of germinal center B cells (22,23) and that CD40 signaling activates the noncanonical NF-kB pathway in a NIK-dependent manner, it is likely that the reductions in germinal center B cells upon acute NIK deletion are a result of the abrogation of NIK-mediated noncanonical NF-kB pathway activation downstream of CD40L/CD40 signaling.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Thus, the differences in secondary lymphoid organ phenotypes between our NIK KO/KO mice and NIK aly/aly mice, as well as the other NIK-deficient mouse strain, may arise from Upon acute deletion of NIK in adult mice using our conditional NIK KO allele, we observed the abrogation of noncanonical NF-kB signaling, as assessed by p52 production, and a resulting reduction in B cell numbers in lymph nodes and spleen. These reductions in B cell populations are similar to what was observed upon blockade of BAFF signaling in adult mice (52) produced in BAFF-deficient and BR3/BAFF-R-deficient mice (61), these effects of NIK deletion likely reflect roles for NIK and the noncanonical NF-kB pathway in non-BAFF-driven biology. Given that CD40L/CD40 signaling is required for germinal center formation and the production of germinal center B cells (22,23) and that CD40 signaling activates the noncanonical NF-kB pathway in a NIK-dependent manner, it is likely that the reductions in germinal center B cells upon acute NIK deletion are a result of the abrogation of NIK-mediated noncanonical NF-kB pathway activation downstream of CD40L/CD40 signaling.…”
Section: Discussionsupporting
confidence: 57%
“…7C, 7D). These effects were specific to B cells, because CD4 + T cell numbers did not change (data not shown) and were very similar to the published effects of BAFF inhibition on B cell populations in adult mice (20,52). Similar effects on B cell populations in the spleen, including marginal zone B cells, also were observed upon acute NIK deletion, although NIK-specific effects at early time points could not be distinguished from nonspecific Cre effects that were observed in Rosa26-CreER T2+ NIK WT/WT control mice (data not shown).…”
Section: Nik Is Required For Baff-mediated B Cell Survival But Not CDsupporting
confidence: 65%
“…Показано, что TACI-рецепторы оказывают негативное воздействие на популяцию периферических В-клеток [31]. При введении BAFF-R-антител мышам выявляется истощение различных популяций В-клеток путем ингибирования BAFF-сигналов и активации ан-тителозависимой клеточной цитотоксичности [32].…”
unclassified
“…Animal and clinical studies of SLE pathogenesis have revealed that B lymphocyte stimulating factor (BLyS) may promote the activation and proliferation of B-lymphocytes, which leads to the production of large amounts of immunoglobulins and autoantibodies (12,13). Immunologic injury is caused by formation of immune complexes, complement-mediated cytolysis, opsonophagocytosis and antibody-mediated cell-dependent cytotoxicity (14).…”
Section: Introductionmentioning
confidence: 99%